Clinical Features of 24 Patients With Rebound‐Associated Vertebral Fractures After Denosumab Discontinuation: Systematic Review and Additional Cases. (13th March 2017) - Anastasilakis, Athanasios D; Polyzos, Stergios A; Makras, Polyzois; Aubry‐Rozier, Berengere; Kaouri, Stella; Lamy, Olivier
ABSTRACT: We aimed to study the clinical and imaging characteristics of patients sustaining vertebral fractures after denosumab discontinuation. For this purpose, we conducted a computerized advanced literature search that identified 13 published cases, and we additionally included another 11 new cases from our centers. Twenty‐four postmenopausal women with vertebral fracture(s) after denosumab discontinuation, experiencing 112 fractures in total, were analyzed. The mean number of fractures per patient was 4.7. The most commonly affected vertebrae were T12 and L1. All fractures occurred 8 to 16 months after the last denosumab injection. Eighty‐three percent of the patients were treatment naïve, whereas 33% had prevalent vertebral fractures. Five (23%) patients were on concurrent aromatase inhibitor treatment. When patients were divided according to treatment duration with an arbitrary cut‐off of 2 years, those with ≤2 years of denosumab treatment had fewer fractures compared with those with >2 years (mean ± SEM fractures 3.2 ± 0.7 versus 5.2 ± 1.4, p = 0.055). Vertebroplasty was used in 5 patients, resulting in additional clinical vertebral fractures in all cases. We conclude that vertebral fracture(s) after denosumab discontinuation are in the majority of patients multiples, and they occur a few months after the effect of the last dose is depleted. Therefore, patients should not delay or omit denosumab doses. Fractures are typically osteoporotic, located at the lower thoracic and the upper lumbar spine. Vertebroplasty is an unsuccessful treatment strategy for such patients. © 2017 American Society for Bone and Mineral Research.